2020
DOI: 10.1177/0887302x20906470
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Sustainability in Fashion Design Courses Through a Zero-Waste Design Project

Abstract: With the increased importance of learning about sustainability in fashion design curriculum, this article reports the teaching zero-waste design in existing fashion design courses that teach skills needed to create and construct garments. This study documents the development and delivery of a zero-waste design project in two different levels of fashion design courses. Data were collected before and after the zero-waste design project implementation. By learning about zero-waste design, students’ interest in su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 26 publications
0
24
0
1
Order By: Relevance
“…Therefore, students in textiles and clothing programs in higher education are both consumers and future professionals who will know to effect sustainable industry practices through their innovations and purchases. Research regarding educating students about environmental sustainability suggests that skills can be improved when students have a semester-long exposure to topics instead of just short introductions within another module or course (Connell & Kozar, 2012;Gam & Banning, 2020). There need to study the structure and organization of the integrated textile and clothing complex and its strategic 6 The Chitrolekha Journal, Vol.…”
Section: Impact Of Industry On the Environmentmentioning
confidence: 99%
“…Therefore, students in textiles and clothing programs in higher education are both consumers and future professionals who will know to effect sustainable industry practices through their innovations and purchases. Research regarding educating students about environmental sustainability suggests that skills can be improved when students have a semester-long exposure to topics instead of just short introductions within another module or course (Connell & Kozar, 2012;Gam & Banning, 2020). There need to study the structure and organization of the integrated textile and clothing complex and its strategic 6 The Chitrolekha Journal, Vol.…”
Section: Impact Of Industry On the Environmentmentioning
confidence: 99%
“…The various goals for the inclusion of sustainability issues in curricula, therefore, include making students aware of and understand various issues and challenges linked with sustainability across the product lifecycle and with respect to the fashion market as a whole, and developing their research skills and their ability to critically assess and reflect on the functions and impacts of fashion in the contemporary world and to test and implement a range of approaches [11]. Sustainable fashion design curricula may include various related issues, such as teaching the incorporation of tacit and haptic knowledge of textiles into fashion expression (textile thinking) through students' engagement in producing textiles [25,33], introducing students to different aspects of experimental 'smart' materials and garments (e.g., multisensory, empathic, or bio-smart clothes) [39], or assigning students various zero-waste design projects [40]. A range of approaches, such as collaborative learning, the integration of technology into the teaching and learning process, and connection and cooperation with industry, are applied [26].…”
Section: The Inclusion Of Sustainability-related Themes In Fashion Design Educationmentioning
confidence: 99%
“…DeLong et al (2017) discovered that regarding the design process of repurposing, students found inspiration in the fabrics, yet felt constrained. Gam and Banning (2020) used the PBL method to teach zero-waste design, which resulted in an increase in students' interest in sustainable living and fashion as well as awareness of fabric waste generated in the design and pattern cutting process.…”
Section: Sustainability and Apparel Curriculummentioning
confidence: 99%
“…Their study suggested the lethargy in industry sustainability efforts is largely due to apparel design education having minimal sustainability integration into curriculum. Few studies suggested introducing sustainable design practices in patternmaking courses (Gam & Banning, 2020;Hall & Orzada, 2014).…”
Section: Introductionmentioning
confidence: 99%